2012
DOI: 10.1007/s00417-012-2128-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of lutein in a rat model of retinal detachment

Abstract: BackgroundRetinal detachment (RD) is a leading cause of blindness, and although final surgical re-attachment rate has greatly improved, visual outcome in many macula-off detachments is disappointing, mainly because of photoreceptor cell death. We previously showed that lutein is anti-apoptotic in rodent models of ischemia/reperfusion injury. The objective of this study is to investigate lutein as a possible pharmacological adjunct to surgery.MethodsSubretinal injections of 1.4 % sodium hyaluronate were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…In the present study, we showed that treatment of 20μM of lutein also enhanced Bcl-2 protein expression and abrogated Bax/Bcl-2 ratio after 24 hours of hypoxic injury. More importantly, lutein attenuated cleavage of caspase 3, consistent with our previous finding using an animal model of retinal detachment [36], further strengthening the notion that lutein mediated cytoprotection through regulating the cascade of caspase-associated pathway.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we showed that treatment of 20μM of lutein also enhanced Bcl-2 protein expression and abrogated Bax/Bcl-2 ratio after 24 hours of hypoxic injury. More importantly, lutein attenuated cleavage of caspase 3, consistent with our previous finding using an animal model of retinal detachment [36], further strengthening the notion that lutein mediated cytoprotection through regulating the cascade of caspase-associated pathway.…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, there have been no reports on the effects of lutein on neurons in the brain in a rodent stroke model [27]. In the present study, we found significant interactions between LU and ATO treatments on body weight, liver index, ALT, AST, T-AOC levels, GSH, and MDA contents.…”
Section: Discussionsupporting
confidence: 61%
“…These studies involve neuroprotection and controlling reactive gliosis, one of the major intraretinal changes in PVR. Agents such as melatonin (Iribarne et al, 2007), aspirin (Bazan et al, 2010), tauroursodeoxycholic acid (TUDCA) (Fernandez-Sanchez et al, 2011;Mantopoulos et al, 2011), lutein (Woo et al, 2013), and especially anti-TNF-a (Nakazawa et al, 2011) may provide new therapeutic neuroprotective avenues to treat photoreceptor degeneration after a RD. They may also interfere at the same time with the glial processes that occur after an ischemic event in the retina (Fernandez-Bueno et al, 2013a), much like that which occurs in the CNS (Alonso- Alconada et al, 2013;Bae et al, 2006).…”
Section: A Look Into the Futurementioning
confidence: 99%